Buddhist Leadership Development : Virtues of the King - Sricharumedhiyan, Dr. Chakkree (Journal for Developing the Social and Community, 2018)
Leadership is one of the important methods to develop the organizations. It is the indicators to measure the application of the leaders’ policy to the subordinators’ performance. Everyone in the organizations is important to push every business in the organizations into the successful goal. So, good leadership is required to develop the organizations. Good leadership is consisted with smart thinking, negotiating, and living.